A 2D finite element based on an enriched kinematics for nonlinear analysis of masonry walls. (2019) - Addessi, Daniela; Sacco, Elio
This paper presents a kinematic enriched finite element model for nonlinear analysis of brick masonry walls loaded in their plane. The finite element accounts for the transverse deformation of the wall and permits to reproduce mortar-brick interaction in wall thickness direction. Non-local constitutive relationships are considered both for mortar and bricks, adopting a damage-friction law for the mortar and an isotropic damage model for the bricks, both accounting for tensile failure mechanisms. A numerical procedure is developed for evaluation of damage and friction in mortar and brick materials. Numerical applications are presented, comparing results obtained by the proposed finite element with experimental outcomes.